Effects of Porosity on the Fatigue Behaviour of AlZn10Si8Mg Casting Alloys in a High Cycle Region. (2017) - Závodská, Denisa; Tillová, Eva; Guagliano, Mario; Chalupová, Mária; Kuchariková, Lenka
Abstract: The fatigue behaviour of AlZn10Si8Mg cast alloy used in an automotive industry and consequently effect of porosity was investigated for present study. The study was exploring for a lifetimes as long as 106 cycles using rotating bending fatigue device operating at 30 Hz, at a room temperature 20±5 °C. The tested specimen's fracture surfaces and fracture profiles were observed with the use of a scanning electron microscope (SEM) and optical microscope to determine the fatigue crack initiation sites and porosity. A correlation was made between the sample fatigue life and the distribution of the pores and Fe-rich needle-like phases which initiated the fatigue crack. It was shown that fatigue life decreases as the surface pore size increases and that the crack initiation site contains multiple pores or consists of a spongy structure. Main factor for decreasing the fatigue life are these castings defects since 90% of the samples examined tended to fracture as a result of the casting defects.